POSTOPERATIVE INFECTIOUS COMPLICATIONS IN PATIENTS WITH URINARY DISEASE - A. Ch. Usupbaev; B. A. Kabaev; A. S. Imankulova; N. Zh. Sadyrbekov; K. S. Cholponbaev; A. A. Usupbaeva (Исследования и практика в медицине)
The large proportion of postoperative infectious complications in urological hospitals makes extremely urgent the problem of its control. The high level of these complications in the postoperative period in patients with urolithiasis is caused by various endo- and exogenous factors.Purpose. To determine the frequency, structure, and features of postoperative infectious complications in patients with urolithiasis in urological hospitals.Materials and methods. As an object of research we used a medical card 232 of the operated patients with urolithiasis, which were copied out in individual registration card. Of 232 patients with urolithiasis 48.3% were men, their average age was 44.5 ± 9.4 years. Female patients were slightly larger (51.7%), respectively, the average age was 44.9 ± 8.1 years.Results. The most common postoperative infectious complications in urolithiasis was infection in the area of surgical intervention (36,2%), acute urethritis (20,7%), acute pyelonephritis (14.7 per cent), paranephritis (9,5%), acute orhoepididimit (7,8%), acute cystitis (6%), pionephrosis (3,4%), urosepsis (1.7 percent). In the etiological structure of infectious agents associated with medical care with the highest frequency, microorganisms of genera Escherichia coli (43%), Proteus (9.5%), Staphilococcus spp were isolated. (8.3%) and Staphilococcus aureus (8.3%), and in 11.9% of cases, the Association of microorganisms. Analysis of the etiological structure of genera of the family Enterobacteriaceae resistant to β-lactam antibiotics showed that 63.2% of the amount to the genus strain of E. coli, 21% Proteus and 15.8% Klebsiella.Conclusion. The data obtained indicate the need for research on the prevalence of resistant strains of microorganisms, the introduction of more speciﬁ c, sensitive methods and monitoring. This will increase the eﬀectiveness of treatment, reduce the risk of the spread of resistant strains and increase nosocomial infections.